Production and Comprehension of Prosodic Markers in Sign Language Imperatives - Brentari, Diane; Falk, Joshua; Giannakidou, Anastasia; Herrmann, Annika; Volk, Elisabeth; Steinbach, Markus (Frontiers in Psychology, 2018)
In signed and spoken language sentences, imperative mood and the corresponding speech acts such as for instance, command, permission or advice, can be distinguished by morphosyntactic structures, but also solely by prosodic cues, which are the focus of this paper. These cues can express paralinguistic mental states or grammatical meaning, and we show that in American Sign Language (ASL), they also exhibit the function, scope, and alignment of prosodic, linguistic elements of sign languages. The production and comprehension of prosodic facial expressions and temporal patterns therefore can shed light on how cues are grammaticalized in sign languages. They can also be informative about the formal semantic and pragmatic properties of imperative types not only in ASL, but also more broadly. This paper includes three studies: one of production (Study 1) and two of comprehension (Studies 2 and 3). In Study 1, six prosodic cues are analyzed in production: temporal cues of sign and hold duration, and non-manual cues including tilts of the head, head nods, widening of the eyes, and presence of mouthings. Results of Study 1 show that neutral sentences and commands are well distinguished from each other and from other imperative speech acts via these prosodic cues alone; there is more limited differentiation among explanation, permission, and advice. The comprehension of these five speech acts is investigated in Deaf ASL signers in Study 2, and in three additional groups in Study 3: Deaf signers of German Sign Language (DGS), hearing non-signers from the United States, and hearing non-signers from Germany. Results of Studies 2 and 3 show that the ASL group performs significantly better than the other 3 groups and that all groups perform above chance for all meaning types in comprehension. Language-specific knowledge, therefore, has a significant effect on identifying imperatives based on targeted cues. Command has the most cues associated with it and is the most accurately identified imperative type across groups—indicating, we suggest, its special status as the strongest imperative in terms of addressing the speaker's goals. Our findings support the view that the cues are accessible in their content across groups, but that their language-particular combinatorial possibilities and distribution within sentences provide an advantage to ASL signers in comprehension and attest to their prosodic status.